303 views
5 votes
Evaluate ( f g )(x) if f(x) = 3x2 + 3 and g(x) = 3x – 1 when x = 2.

1 Answer

3 votes

Answer:


(fg)(x) = 75

Explanation:

Given


f(x) = 3x^2 + 3


g(x) = 3x - 1

Required

Evaluate (fg)(x) for x = 2

In algebra functions


(fg)(x) = f(x) * g(x)

Substitute values for f(x) and g(x)


(fg)(x) = (3x^2 + 3) * (3x - 1)

Substitute 2 for x


(fg)(x) = (3*2^2 + 3) * (3*2 - 1)


(fg)(x) = (3*4 + 3) * (6 - 1)


(fg)(x) = (12 + 3) * (5)


(fg)(x) = (15) * (5)


(fg)(x) = 15 * 5


(fg)(x) = 75

User Sotto
by
5.0k points